2017
DOI: 10.3389/fpsyg.2017.01454
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Emotion on Learning and Memory

Abstract: Emotion has a substantial influence on the cognitive processes in humans, including perception, attention, learning, memory, reasoning, and problem solving. Emotion has a particularly strong influence on attention, especially modulating the selectivity of attention as well as motivating action and behavior. This attentional and executive control is intimately linked to learning processes, as intrinsically limited attentional capacities are better focused on relevant information. Emotion also facilitates encodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
605
0
60

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 913 publications
(675 citation statements)
references
References 177 publications
10
605
0
60
Order By: Relevance
“…The critical question for each of us and for the human society as a whole is, how the brain decides what to memorize and what to forget, and how we can influence this decision most efficiently. Emotional labels can be influential 14 . Also, what repeatedly occurs is worth being remembered (e.g.…”
mentioning
confidence: 99%
“…The critical question for each of us and for the human society as a whole is, how the brain decides what to memorize and what to forget, and how we can influence this decision most efficiently. Emotional labels can be influential 14 . Also, what repeatedly occurs is worth being remembered (e.g.…”
mentioning
confidence: 99%
“…According to the literature, visual stimuli have been found effective to use in lectures and written texts in order to improve hand hygiene behavior and it has also been suggested that animated visual elements may have a better and more direct effect compared with static pictures [44][45][46]. Likewise, emotional events are memorized more precisely and for a longer duration compared with neutral events, making them beneficial aspects to consider in education and memory [47]. In line with the possible advantages mentioned for these symbols, the first pilot intervention to assess the impact of emoticons on hand hygiene was performed by Gaube et al in a German hospital [48].…”
Section: The Example Of Hand Hygienementioning
confidence: 99%
“…Örneğin bireyler öfkeli hissettiklerinde saldırma davranışını ya da tiksinme hissettiklerinde kusma davranışı sergileyebilirler (Fredrickson, 2004). Bir diğer ifadeyle bireyler, duygusal deneyimleri çerçevesinde tepki gösterir, karar alır ve öğrenirler (Shuck, Albornoz ve Winberg, 2007;Tyng, Amin, Saad ve Malik, 2017;Um, Plass, Hayward ve Homer, 2012;Watanabe, Sakagami ve Haruno, 2013). Etkili bir öğrenme ortamının oluşmasında öğrencilerin olumlu duygularının harekete geçirilmesi oldukça önemlidir.…”
Section: Duyguunclassified